2005
DOI: 10.1186/1471-2156-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screening for genes whose deletions confer sensitivity to mutagenic purine base analogs in yeast

Abstract: Background: N-hydroxylated base analogs, such as 6-hydroxylaminopurine (HAP) and 2-amino-6-hydroxylaminopurine (AHA), are strong mutagens in various organisms due to their ambiguous base-pairing properties. The systems protecting cells from HAP and related noncanonical purines in Escherichia coli include specialized deoxyribonucleoside triphosphatase RdgB, DNA repair endonuclease V, and a molybdenum cofactor-dependent system. Fewer HAP-detoxification systems have been identified in yeast Saccharomyces cerevisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…The YJL055W gene is known to confer resistance to 5-FOA when overexpressed, and further testing showed that it also confers resistance to 5-FU [19]. Conversely, a yjl055w mutant is sensitive to purine analogs [20]. It has therefore been proposed that YJL055W may function in detoxification of base analogs [19].…”
Section: Resultsmentioning
confidence: 99%
“…The YJL055W gene is known to confer resistance to 5-FOA when overexpressed, and further testing showed that it also confers resistance to 5-FU [19]. Conversely, a yjl055w mutant is sensitive to purine analogs [20]. It has therefore been proposed that YJL055W may function in detoxification of base analogs [19].…”
Section: Resultsmentioning
confidence: 99%
“…The results of numerous global screens of sensitivity to various genotoxic stress are also available [9], [42]. There is only modest overlap of our gene list with any of the published studies, but they are also quite dissimilar (see Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that the DIAL probe may be a substrate for some minor activity, particularly at long reaction times as seen here. Several other genes, in addition to HAM1 , are involved in protection from HAP in yeast ( 62 ). Future characterization of background activity in extracts of yeast double mutants with deletion of ITPA and these genes or genes encoding other phosphatases will shed light on additional enzymes that participate in cleansing the nucleotide pool of deamination damage in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%